Answer:
its 3 :)
Explanation:
Simplifying
8 + -1(4x + 7) = 5(x + 6) + -2
Reorder the terms:
8 + -1(7 + 4x) = 5(x + 6) + -2
8 + (7 * -1 + 4x * -1) = 5(x + 6) + -2
8 + (-7 + -4x) = 5(x + 6) + -2
Combine like terms: 8 + -7 = 1
1 + -4x = 5(x + 6) + -2
Reorder the terms:
1 + -4x = 5(6 + x) + -2
1 + -4x = (6 * 5 + x * 5) + -2
1 + -4x = (30 + 5x) + -2
Reorder the terms:
1 + -4x = 30 + -2 + 5x
Combine like terms: 30 + -2 = 28
1 + -4x = 28 + 5x
Solving
1 + -4x = 28 + 5x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-5x' to each side of the equation.
1 + -4x + -5x = 28 + 5x + -5x
Combine like terms: -4x + -5x = -9x
1 + -9x = 28 + 5x + -5x
Combine like terms: 5x + -5x = 0
1 + -9x = 28 + 0
1 + -9x = 28
Add '-1' to each side of the equation.
1 + -1 + -9x = 28 + -1
Combine like terms: 1 + -1 = 0
0 + -9x = 28 + -1
-9x = 28 + -1
Combine like terms: 28 + -1 = 27
-9x = 27
Divide each side by '-9'.
x = -3
Simplifying
x = -3